Challenges of Inclusion of Primary School Pupils with Hearing Impairment in Physical Activities in Tanzania - Mlay, Janeth Danford; Mabagala, Stephen Mabagala; Ndabi, Joyce Sifa (Papers in Education and Development, 2023)
Pupils with hearing impairment are not adequately included in physical activities in primary school globally but more so in the global South. This study was conducted in a selected primary school in Tanzania. It is a qualitative study that employed an embedded single case design to gain indepth understanding of the study. The study was guided by Bronfenbrenner system theory (1979). The sample comprised thirty eight purposively selected participants. Data were collected through interview, documentary review, and observation schedule methods. The data were thematically analysed. Findings revealed specific and general challenges such as lack of sign language skills used during physical activity, poor aesthetic attributes, inaccessible physical activity facilities and equipment, stigmatization, unsafe play facilities and lack of physical activity programme. The results revealed that the school was insufficiently equipped for inclusion. Based on the findings of this study, it is recommended that to solve the revealed challenges schools should provide a conducive environment for inclusion of pupils with hearing impairment in physical activities. Keywords: deaf, hearing impairment, inclusion, school environment